2008
DOI: 10.1590/s0100-72032008000200003
|View full text |Cite
|
Sign up to set email alerts
|

A expressão da proteína p16 e herpes simples vírus tipo 2 em lesões pré-neoplásicas e neoplásicas do colo do útero

Abstract: a progressive increase of reactivity ratios of the studied immunohistochemical markers as a function of lesion severity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many recent studies have found the importance of p16 and p53 in cervical neoplasia 9,[12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . The vast majority rated the immunomarker positivity percentage for the presence of cervical intraepithelial neoplasia and correlated with the lesion severity 9,12,13,17,18,[21][22][23][24][25][26][27][28][29] . However, few studies related immune reaction with disease recurrence and/or prognosis 13.14-31 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Many recent studies have found the importance of p16 and p53 in cervical neoplasia 9,[12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . The vast majority rated the immunomarker positivity percentage for the presence of cervical intraepithelial neoplasia and correlated with the lesion severity 9,12,13,17,18,[21][22][23][24][25][26][27][28][29] . However, few studies related immune reaction with disease recurrence and/or prognosis 13.14-31 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…For instance, one alternative approach is based on immunocytochemical detection of cellular proteins, such as p53, p16 or HPV viral antigens [12-15 ]. Reports using these markers show that although the marker may be expressed in all grades of cervical neoplasia, in some cases, a particular grade may exhibit no demonstrable expression.…”
Section: Discussionmentioning
confidence: 99%
“…), long term use of oral contraceptives, intrauterine device use, multiple full-term pregnancies, young age at full-term pregnancy and poverty. [2][3][4] Human Herpesviruses (HHVs) can induce cell transformation by production of oncogenic proteins or by interacting with cell replication, which are important steps for cancer development 5 For many years, CMV was one of the HHVs that was thought to have a role in the development of cervical lesions. 6 CMV infects between 50 to 85% of the worldwide population by early adulthood.…”
Section: Introductionmentioning
confidence: 99%